Effects of anti-oxidant additives on microscopic and oxidative parameters of Angora goat semen following the freeze-thawing process - Atessahin, Ahmet; Bucak, Mustafa Numan; Tuncer, Puerhan Barbaros; Kizil, Meltem (Elsevier Science Bv, 2008)
The anti-oxidant system of reduced glutathione (GSH), glutathione peroxidase (GSH-PX), catalase (CAT), and superoxide dismutase (SOD) has been described as a defense functioning mechanism against lipid peroxidation (LPO) in semen, and is important in maintaining sperm motility and viability. This anti-oxidant capacity of sperm cells may be insufficient in preventing LPO during the freeze-thawing process. The aim of this study was thus to determine the influence of varying doses of anti-oxidant additives on standard semen parameters, lipid peroxidation and anti-oxidant activities after the freeze-thawing of goat semen. Ejaculate samples (artificial vagina) obtained from 4 mature Angora goats were evaluated and pooled at 37 degrees C. The semen samples diluted with a Tris-based extender, containing taurine (25, 50, 75 mM), trehalose (25, 50, 75 mM), and cysteine (5, 10, 15 MM), and an extender containing no anti-oxidant additives (control) were again evaluated. Diluted semen was cooled down to 5 degrees C and frozen in 0.25 ml French straws, prior to being stored in liquid nitrogen. Frozen straws were thawed in a water bath (37 degrees C) for 30s for microscopic sperm evaluation. Upon evaluation of parameters for semen quality, the use of a Tris-based extender supplemented with anti-oxidant additives was found to cause no significant improvement in sperm mortality, when compared to the controls. Increasing doses of taurine and trehalose decreased (P < 0.05) the sperm motility following the freeze-thawing of the goat semen. In biochemical assays, the application of taurine (75 mM) produced the lowest level of malondialdehyde (MDA) (4.46 +/- 0.31 nmol/ml), compared to the controls (P < 0.001). Lower GSH levels were higher in the groups in which cysteine was included at 10 and 15 mM (3.27 +/- 10.11 and 3.45 +/- 0.28 nmol/ml)-compared to the group which received 5 mM cysteine, as well as the controls (2.27 +/- 0.08 and 2.50 +/- 0.08 nmol/ml respectively, P < 0.001). Compared to the controls, taurine at a concentration of 25 and 75 mM, and increasing doses (50 and 75 mM) of trehalose, significantly increased the GSH-PX activity (P < 0.01). The maintenance of CAT activity was demonstrated to be higher with the addition of 10 and 15 mM cysteine, compared to the other groups (P < 0.001). Vitamin A (VitA) levels were significantly higher, compared to the controls (267.34 +/- 9.68 mg/dl and 267.34 9.68 mg/dl, respectively), when 25 mM taurine (329.61 +/- 6.35 mg/dl) and 10 mM (318.64 +/- 6.34 mg/dl) cysteine was added to the extender (P < 0.001). The results of this study provide a new approach to the cryopreservation of Angora goat semen and could contribute to the improvement of this technology in the goat industry. Published by Elsevier B.V.
Keywords: Angora goat; semen; anti-oxidants; cryopreservation; oxidative stress parameters